Giant adrenal pseudocyst removed using robot‐assisted surgery. Issue 2 (12th January 2023) - Ohzeki, Takayuki; Kita, Hiroyuki; Kunishige, Remon; Hayashi, Taiji; Nishioka, Tsukasa
Abstract : Introduction: Adrenal cysts are relatively rare and often asymptomatic. Surgical treatment is indicated for symptomatic cases with cysts >6 cm, suspected bleeding, and those that cannot be distinguished from malignant illness based on imaging findings. There have often been cases of giant cysts that were difficult to treat using laparoscopic surgery. Case presentation: A 39‐year‐old woman presented with fever and upper abdominal pain. Abdominal computed tomography and magnetic resonance imaging revealed a 95 × 80‐mm left adrenal cyst. As malignant disease could not be ruled out, and the patient was symptomatic, we opted for robot‐assisted left adrenalectomy. The pathological findings indicated an adrenal pseudocyst. Conclusions: This is the second report of the successful robot‐assisted removal of a giant adrenal cyst.